Answer:
Option A. x < -4
Explanation:
The given function is f(x) = -(x + 6)(x + 2)
General form of the function will be,
f(x) = -(x² + 2x + 6x + 12)
= -(x² + 8x + 12)
Vertex form of the function will be,
f(x) = -[x² + 2(4)x + 12]
= -[(x² + 2(4)x + 16) - 16 + 12]
= -(x + 4)² + 4
Therefore, parabola for the function above will open down with vertex (-4, 4) as shown in the graph attached.
Graph shows the function is increasing in x < -4 and decreasing in x > -4.
Therefore, Option A. is the correct answer.